Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Hi can you help me solve this: I have proved that $p(1)$ is true and am now assuming that $p(k)$ is true. I just don't know how to show $p(k+1)$ for both sides?

share|improve this question
    
Do you mean $\sum_{r=1}^n \frac{1}{r(r+1)}=\frac{n}{n+1}$? –  Ben Millwood Jan 7 '13 at 21:45
    
Yes! sorry I do not know how to format like that. –  maxmitch Jan 7 '13 at 21:50
    
You can learn some here and at some of the references that you’ll find there. –  Brian M. Scott Jan 7 '13 at 21:52
    
Thanks I have just learnt it! :) –  maxmitch Jan 7 '13 at 22:03
add comment

4 Answers 4

Hint: $$\sum_{r=1}^{k+1}\frac{1}{r(r+1)}=\sum_{r=1}^{k}\frac{1}{r(r+1)}+\frac{1}{(k+1)((k+1)+1)}.$$ Now use the inductive hypothesis and see if that gets you anywhere.

share|improve this answer
add comment

$$\sum_{r=1}^{n}\frac{1}{r(r+1)}=\frac{n}{n+1}$$ for $n=1$ we have $\frac{1}{1(1+1)}=\frac{1}{1+1}$ suppose that $$\sum_{r=1}^{k}\frac{1}{r(r+1)}=\frac{k}{k+1}$$ then $$\sum_{r=1}^{k+1}\frac{1}{r(r+1)}=\sum_{r=1}^{k}\frac{1}{r(r+1)}+\frac{1}{(k+1)(k+2)}=$$ $$=\frac{k}{k+1}+\frac{1}{(k+1)(k+2)}=\frac{k(k+2)+1}{(k+1)(k+2)}=$$ $$=\frac{k^2+2k+1}{(k+1)(k+2)}=\frac{(k+1)^2}{(k+1)(k+2)}=\frac{k+1}{k+2}=\frac{(k+1)}{(k+1)+1}$$

share|improve this answer
add comment

If you want to do it by a conventional "blind" induction, suppose that for a certain $k$ we have $$\sum_1^k \frac{1}{r(r+1)}=\frac{k}{k+1}.\tag{$1$}$$ We want to prove that $$\sum_1^{k+1} \frac{1}{r(r+1)}=\frac{k+1}{k+2}.\tag{$2$}$$ Note that the left-hand side of $(2)$ is the left-hand side of $(1)$, plus $\dfrac{1}{(k+1)(k+2)}$.

So we want to prove that $$\frac{k}{k+1}+\frac{1}{(k+1)(k+2)}=\frac{k+1}{k+2}.\tag{$3$}$$ It seems reasonable to manipulate the left-hand side of $(3)$ and see whether we get the right-hand side. A common manipulation is to bring the expression to the common denominator $(k+1)(k+2)$. We get $$\frac{k(k+2)}{(k+1)(k+2)}+\frac{1}{(k+1)(k+2)}.$$ This is equal to $\dfrac{k^2+2k+1}{(k+1)(k+2)}$.

But the numerator is equal to $(k+1)^2$. Cancel a $k+1$.

Remark: The algebra at the end is neater, and closer to the informal "telescoping" argument, if we observe that $\dfrac{1}{(k+1)(k+2)}=\dfrac{1}{k+1}-\dfrac{1}{k+2}$. Thus $$\frac{k}{k+1}+\frac{1}{(k+1)(k+2)}=\frac{k}{k+1}+ \frac{1}{k+1}-\frac{1}{k+2}=1-\frac{1}{k+2}=\frac{k+1}{k+2}.$$

share|improve this answer
add comment

HINT:

$$\frac1{r(r+1)}=\frac1r-\frac1{r+1}$$

and

$$\frac{n}{n+1}=1-\frac1{n+1}\;.$$

share|improve this answer
    
I suggest that the downvoter think a bit more about how these two observations can be incorporated into a proof by induction. (Indeed, one has only to look at André’s remark.) –  Brian M. Scott Jan 7 '13 at 22:35
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.